2020
DOI: 10.1186/s40035-020-00191-5
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of gait in Parkinson’s disease: pathophysiology, risk factors and treatments

Abstract: Background: Freezing of gait (FOG) is a common, disabling symptom of Parkinson's disease (PD), but the mechanisms and treatments of FOG remain great challenges for clinicians and researchers. The main focus of this review is to summarize the possible mechanisms underlying FOG, the risk factors for screening and predicting the onset of FOG, and the clinical trials involving various therapeutic strategies. In addition, the limitations and recommendations for future research design are also discussed. Main body: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 172 publications
(322 reference statements)
5
100
1
10
Order By: Relevance
“…Besides, the clinical feature was associated with many other non-motor symptoms, including daytime sleepiness. While dopaminergic neurons were mostly depleted in PD patients 6 , studies suggested that fatigue was most likely to result from disruption of nondopaminergic pathways 33 . Pavese N et al found that the serotoninergic dysfunction in basal ganglia and limbic circuits was associated with fatigue, which also supported the observed associations between fatigue and other non-motor symptoms 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the clinical feature was associated with many other non-motor symptoms, including daytime sleepiness. While dopaminergic neurons were mostly depleted in PD patients 6 , studies suggested that fatigue was most likely to result from disruption of nondopaminergic pathways 33 . Pavese N et al found that the serotoninergic dysfunction in basal ganglia and limbic circuits was associated with fatigue, which also supported the observed associations between fatigue and other non-motor symptoms 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have concentrated on complex determinants and pathophysiology of FoG 6 . Only a few studies have made efforts to predict FoG onset, especially in newly diagnosed PD patients [7][8][9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FoG is defined as “brief, episodic absence or marked reduction of forward progression of the feet despite the intention to walk” and typically occurs on initiating gait or on turning while walking [ 2 ]. Several therapeutic approaches have been employed in clinical studies and medical practice in order to improve FoG, including: pharmacological therapy; brain, spinal cord and vagus nerve stimulation; and physiotherapeutic approaches using wearable cueing devices, treadmill training, walk-bicycle, or obstacle aquatic training with variable clinical benefit [ 3 ]. Despite the wide number of proposed therapies, FoG is still difficult to treat because many patients do not have a complete response to dopaminergic therapy [ 2 ] and neurostimulation techniques, although promising, may require invasive and expensive technology not always available [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several therapeutic approaches have been employed in clinical studies and medical practice in order to improve FoG, including: pharmacological therapy; brain, spinal cord and vagus nerve stimulation; and physiotherapeutic approaches using wearable cueing devices, treadmill training, walk-bicycle, or obstacle aquatic training with variable clinical benefit [ 3 ]. Despite the wide number of proposed therapies, FoG is still difficult to treat because many patients do not have a complete response to dopaminergic therapy [ 2 ] and neurostimulation techniques, although promising, may require invasive and expensive technology not always available [ 3 ]. In this scenario, physiotherapeutic approaches may be easier to apply with a lower risk of side effects and potential cardiovascular benefits.…”
Section: Introductionmentioning
confidence: 99%